Malaysia Economic Monitor, April 2012 : Modern Jobs - World Bank (World Bank, Bangkok, 2017)
The Malaysian economy grew robustly in 2011, outperforming forecasts. Growth was driven by domestic demand. Public consumption picked up more than expected toward the end of the year and fixed investment was also buoyant on higher investments by public and private companies. Private consumption spending remained strong, sustained by solid consumer credit, civil service bonus payments, and firm commodity prices benefiting smallholders. Inventories were a drag on growth as post- financial crisis restocking was completed. There is momentum to the reform agenda, but implementation could be accelerated. The government's transformation programs registered notable progress, but the challenge now is to go beyond quick wins and accelerate the implementation of more difficult, but critical, structural reforms that lie at the core of transforming the economy into a high-income one. Implementation can be assisted by increasing the coordination of related reform efforts (such as safety nets and education), building capacity within the civil service to lead reforms, and working towards consensus in key areas such as educational reform, subsidy rationalization and broadening the tax base.